О сингулярной двухтoчечной задаче для линейного функционально-дифференциального уравнения - Самойленко, А.М.; Ронто, А.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
We give new conditions sufficient for the unique solvability of a singular mixed-type two-point boundary-value problem for systems of linear functional differential equations of the second order.